Laporan Kasus: Hipotiroid Kongenital pada Anak Perempuan Usia 6 Bulan - Sidrah Darma (Syntax Idea)
Congenital hypothyroidism is a common endocrine disorder found in newborn babies. This condition is caused by low or absent production of thyroid hormones, which can lead to physical and cognitive developmental issues in children if not detected and treated promptly. This research aims to investigate the incidence rate of congenital hypothyroidism in 6-month-old girls in a specific population. This study is a retrospective observational study using data from child health records at a leading hospital during a specific time period. The study subjects were female children who had reached 6 months of age at the time of diagnosis. The collected data includes demographic information, birth history, and the results of thyroid hormone screening tests. Out of the total number of 6-month-old girls screened, a certain number of cases of congenital hypothyroidism were diagnosed. The incidence rate of congenital hypothyroidism in 6-month-old girls in this population is X%. Furthermore, the analysis indicates that the mother's age, a family history of thyroid disorders, and certain environmental factors potentially serve as risk factors for the occurrence of congenital hypothyroidism. This research highlights the importance of thyroid hormone screening in 6-month-old girls to early detect congenital hypothyroidism. These findings underscore the need for awareness of the importance of early detection and appropriate intervention to prevent negative impacts on the physical and cognitive development of children. Further research is needed to better understand the risk factors associated with this condition and to develop more effective prevention strategies.